2020
DOI: 10.1080/03601277.2020.1714142
|View full text |Cite
|
Sign up to set email alerts
|

Older adult entrepreneurs as mentors of young people neither in employment nor education and training (NEETs). Evidences from multi-country intergenerational learning program

Abstract: Population aging is exacerbating the loss of competences in the workforce and simultaneously young people neither in employment nor in education and training (NEETs) are struggling to be reengaged in employment. These issues, which are deemed priorities for the European policy agenda, could be addressed by triggering active aging dimensions, valuing and exploiting older adult entrepreneurs' knowledge for enhancing youngsters' entrepreneurial attitudes, through mentoring. This paper reports the results of a stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…This is reflected in the focus of empirical studies, e.g., [87]. Although entrepreneurs may adopt coaching and mentoring roles in later years, e.g., [88], the respondents in this sample are in the early stages of the "entrepreneurial process", i.e., in the early stages of development as an entrepreneur/intrapreneur.…”
Section: Discussion: Intrapreneurial Fit and Organizational Culturementioning
confidence: 99%
“…This is reflected in the focus of empirical studies, e.g., [87]. Although entrepreneurs may adopt coaching and mentoring roles in later years, e.g., [88], the respondents in this sample are in the early stages of the "entrepreneurial process", i.e., in the early stages of development as an entrepreneur/intrapreneur.…”
Section: Discussion: Intrapreneurial Fit and Organizational Culturementioning
confidence: 99%
“…The quasi-experimental studies, mixed-method study design, and pre-post study [63,65,67,70,71,78,80,84,85,[87][88][89] revealed consistent statistical results on the interventions' gains. There were global improvements between pre-and post-intervention.…”
Section: Results Of Interventionsmentioning
confidence: 96%
“…These studies are focused on programs that specifically target the development of ES [62,63,65,66,87], the development of business plans and models [73,74,78,91], and the promotion of skills within the scope of social entrepreneurship and sustainability [64,81,82] in the scope of agriculture [77,88] and of technologies [63,87,90]. Some specific competences also stand out, such as teamwork [63,67,73,81,86,89], self-efficacy [64,70,72,74,78,84], leadership [86,88], self-confidence [64,73,81], proactivity and initiative [64,66,84], innovation [64,66,68,84], problem solving [66,72,86], empathy [64,81], self-esteem [8...…”
Section: Characterization Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been accumulating attention paid and efforts made to investigate the advantages of having older and younger generations learn together across different countries (e.g., Boström, 2014 ; Franz and Scheunpflug, 2016 ; Spiteri, 2016 ; Gerpott et al, 2017 ; McKee and Scheffel, 2019 ; Sun et al, 2019 ; Yin et al, 2019 ; Santini et al, 2020 ). For example, Santini et al ( 2020 ) conducted an intergenerational learning program in Germany, Italy, and Slovenia focusing on the field of organization and employment. During the program, the senior adults acted as mentors, and their entrepreneurial knowledge was valued for fostering the youngsters' entrepreneurial attitudes.…”
Section: Introductionmentioning
confidence: 99%